Endothelial dysfunction in pathological processes of chronic liver disease during aging. Issue 1 (27th December 2021) - Wan, Ying; Li, Xuedong; Slevin, Elise; Harrison, Kelly; Li, Tian; Zhang, Yudian; Klaunig, James E.; Wu, Chaodong; Shetty, Ashok K.; Dong, X. Charlie; Meng, Fanyin
Abstract: Aging is associated with gradual changes in liver structure and physiological/pathological functions in hepatic cells including hepatocytes, cholangiocytes, Kupffer cells, hepatic stellate cells (HSCs), and liver sinusoidal endothelial cells (LSECs). LSECs are specialized hepatic endothelial cells that regulate liver homeostasis. These cells actively impact the hepatic microenvironment as they have fenestrations and a thin morphology to allow substance exchange between circulating blood and the liver tissue. As aging occurs, LSECs have a reduction in both the number and size of fenestrations, which is referred to as pseudocapillarization. This along with the aging of the liver leads to increased oxidative stress, decreased availability of nitric oxide, decreased hepatic blood flow, and increased inflammatory cytokines in LSECs. Vascular aging can also lead to hepatic hypoxia, HSC activation, and liver fibrosis. In this review, we described the basic structure of LSECs, and the effect of LSECs on hepatic inflammation and fibrosis during aging process. We briefly summarized the changes of hepatic microcirculation during liver inflammation, the effect of aging on the clearance function of LSECs, the interactions between LSECs and immunity, hepatocytes or other hepatic nonparenchymal cells, and the therapeutic intervention of liver diseases by targeting LSECs and vascular system. Since LSECs play an important role in the development of liver fibrosis and the changes of LSEC phenotype occur in the early stage of liver fibrosis, the study of LSECs in the fibrotic liver is valuable for the detection of early liver fibrosis and the early intervention of fibrotic response.